Pulmonary Findings on Computed Tomography in Asymptomatic Total Joint Arthroplasty Patients - Vigdorchik, Jonathan M.; Riesgo, Aldo M.; Lincoln, Denis; Markel, David C. (The Journal of Knee Surgery, 2016)
An increase in the diagnosis of pulmonary embolus (PE) in the early postoperative period has been attributed to the use of multidetector 64-slice computed tomographic (CT) scans. It was suspected that this finding was the result of marrow or fat emboli that are commonly associated with arthroplasty rather than a true venous thromboembolic phenomenon. The purpose of this study was to determine the baseline pulmonary findings in asymptomatic patients after total joint arthroplasty (TJA). Over a 1-year period, an institutional review board-approved prospective study of 20 asymptomatic patients using a multidetector 64-slice CT scanner was performed. Overall, 15 TKAs and 5 total hip arthroplasties were included for analysis. All of the CT scans were negative for PE. There were no signs of microemboli or fat emboli on any scan. No patient went on to develop a PE at 2 years postoperatively. Despite the fact that emboli are created during TJA, if emboli are seen on a CT scan postoperatively, they should be assumed to be real events with clinical sequelae. If pulmonary symptoms develop postoperatively, they should not simply be assumed to be the result of fat or marrow embolism.
Keywords: asymptomatic; pulmonary embolism; total knee arthroplasty